Ruthenium(II)‐Catalyzed C−C Arylations and Alkylations: Decarbamoylative C−C Functionalizations. (5th April 2017) - Moselage, Marc; Li, Jie; Kramm, Frederik; Ackermann, Lutz
Abstract: Ruthenium(II)biscarboxylate catalysis enabled selective C−C functionalizations by means of decarbamoylative C−C arylations. The versatility of the ruthenium(II) catalysis was reflected by widely applicable C−C arylations and C−C alkylations of aryl amides, as well as acids with modifiable pyrazoles, through facile organometallic C−C activation.